Model-based performance study of an industrial single spool gas turbine 9EA-GT by changing the inlet guide vane angle and modifying the compressor map - Alblawi, Adel (Frontiers in Mechanical Engineering, 2024)
In this article, an industrial gas turbine engine with a single spool (single spool 9EA-GT) is discussed, and a thermodynamic model for computing steady-state performance is presented. In addition, a novel component map production method for investigating a gas turbine engine (GTE) is developed for a different compressor and turbine by downloading from the GasTurb 12 tool and scaling to the compressor and turbine’s design points. A system of controlling engine flow capacitance by changing inlet guide vanes (IGVs) is presented. Adjusting the controllable IGV blades can optimize all the engine units by continuously correcting the compressor features map. The airflow via the compressor, which in turn controls the airflow throughout the entire system, is managed by IGVs. The computations for steady-state performance involve two models: steady-state behavior at engine startup (from 65% to 100% speed, without load) and steady-state behavior while loading (continuous speed of 100%). In this model, the challenges brought by the lack of understanding of stage-by-stage performance are resolved by building artificial machine maps using suitable scaling methods to generalized maps derived from the previous research and validating them with experimental observations from real power plants. The engine performance simulation utilizing the maps is carried out using MATLAB. Assessment results are found to be in good agreement with the actual performance data. During a steady start, the control system used in this study decreased the fuel consumption, exhaust gas mass flow rate, and compressor-driven power for the GTE by 9.5%, 19.3%, and 37.5%, respectively, and those variables decreased by 1%, 12.2%, and 19.7%, respectively, when loading the engine.